The Inverted Swallow in Artistic Gymnastics and Its Related Preconditioning Strengthening Exercises: Electromyographic Analysis, Muscle Synergies and Training Implications - Giuseppe Rosaci; Sandro Bartolomei; Silvia Fantozzi; Christoph Schärer (Applied Sciences)
The Inverted Swallow (IS) is a rare isometric upper-body skill in artistic gymnastics. Athletes use Preconditioning Strengthening Exercises (PSEs) to develop the strength necessary to hold the IS at competition rings. However, the specific muscle excitation and synergies typical of the IS and its PSEs remain unexplored. Thus, this study analyzed muscle excitations and synergies during the IS and its five common PSEs. Muscle excitation was recorded from the pectoralis major, latissimus dorsi, triceps brachii, infraspinatus, trapezius, serratus anterior, biceps brachii and posterior deltoid muscles in six elite calisthenics athletes (age: 24.5 ± 3.0 years; height: 168.6 ± 5.8 cm; body mass: 65.0 ± 4.7 kg). Non-Negative Matrix Factorization was used to extract synergies. The results showed a predominant role of the posterior deltoid and triceps brachii during the IS. Significant differences were observed in the muscle excitation of the triceps brachii between the IS and its PSEs (p ≤ 0.001; W = 0.765), and in the posterior deltoid (p = 0.002; W = 0.629). Muscle synergy patterns also differed in simultaneous muscle activation between the IS and its PSEs. These findings provide the first detailed evidence of the characteristics of the IS element, providing insights for optimizing strength training and gymnastics performance.